اخلاقيات القائم بالعلاقات العامة الرقمية - شليق, ميرة; فلوح, جمعية (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
هدفت الدراسة إلى معرفة أبرز الأخلاقيات التي يلتزم بها القائمين بالعلاقات العامة الرقمية في مؤسسة ميناء مستغانم، حيث عالجنا هذا الموضوع من خلال الإشكالية التالية: ما هي الأخلاقيات التي يتمتع بها ممارسو العلاقات العامة الرقمية في مؤسسة ميناء مستغانم؟ وما مدى التزامه بها؟ وبيّنت الدّراسة أن أبرز وظائف العلاقات العامة الرقمية في مؤسسة ميناء مستغانم هي نشر الصور والفيديوهات حول أنشطتها الروتينية وكذلك تنظيم الدورات التّكوينية لمدة 15 يوما داخل المؤسسة حيث كانت مؤسسة ميناء مستغانم هي المؤسسة التي تمّ اختيارها قصد دراسة الحالة، ولتحقيق أهداف الدّراسة تمّ الاعتماد على أداة المقابلة وأداة الملاحظة لجمع البيانات، والتعرف على الوسائل والتقنيات التي تعتمدها في خدماتها (الموقع الإلكتروني، البريد الإلكتروني، الفيس بوك). توصّلت دراستنا إلى مجموعة من النتائج أهمها: يوجد وعي وفهم لدور العلاقات العامة الرقمية في مؤسسة ميناء مستغانم ولكنها غير كافية وليس هناك وعي بأهميتها من طرف القائمين عليها الذين أكّدوا أنه مواكبة للتّطور لا غير.
مؤسسة ميناء مستغانم نموذجا
The study aimed to learn the most prominent ethics that digital public relations practitioners adhere to at the Port of Mustaganem Foundation, where we addressed this issue through the following problems: What ethics do digital public relations practitioners enjoy at the Port of Mustaganim Foundation? How committed is he? The study showed that the most prominent functions of digital PR at Port Mostaganem Foundation are to publish photos and videos about their routine activities as well as to organize 15 days of formative courses within the institution where Port Mostaganem Foundation was the chosen institution for case study In order to achieve the objectives of the study, the corresponding tool and the observation tool were used to collect data, And learn about the means and techniques you adopt in their services (website, email, Facebook). Our study has reached a series of results, the most important of which are: There is awareness and understanding of the role of digital PR in the Port Mustaganem institution but it is insufficient and there is no awareness of its importance on the part of those who have confirmed that it is only in keeping with development.
Keywords: العلاقات العامة الرقمية- الأخلاقيات- القائم بالعلاقات العامة.; Digital PR - Ethics - Public Relations